Self-validating optimum currency areas - Giancarlo Corsetti; Paolo Pesenti (Federal Reserve Bank of New York, 2002)
A currency area can be a self-validating optimal policy regime, even when monetary unification does not foster real economic integration and intra-industry trade. In our model, firms choose the optimal degree of exchange rate pass-through to export prices while accounting for expected monetary policies, and monetary authorities choose optimal policy rules while taking firms' pass-through as given. We show that there exist two equilibria, each of which defines a self-validating currency regime. In the first, firms preset prices in domestic currency and let prices in foreign currency be determined by the law of one price. Optimal policy rules then target the domestic output gap, and floating exchange rates support the flex-price allocation. In the second equilibrium, firms preset prices in consumer currency, and a monetary union is the optimal policy choice for all countries. Although a common currency helps synchronize business cycles across countries, flexible exchange rates deliver a superior welfare outcome.
Keywords: E5; F4; 330; optimum currency areas; monetary union; optimal cyclical monetary policy; nominal rigidities; exchange rate pass-through; Optimaler Währungsraum; Exchange Rate Pass-Through; Theorie